Study of shear for steel fibre reinforced concrete(SFRC) with ratio 0.15%, 0.25%, 0.35%, 0.45% and 0.55% - Ahmad Izzudin, Ismail (2010)
Steel Fibre Reinforced Concrete can be manufactured by adding steel fibre to a concrete mix design.Steel fibres were adding to the concrete in order to get more strength. The concrete grade of 30 N/mm² was used during the preparation of the concrete mixture for the usage of normal concrete as the control sample and sample with 0.15%,0.25%, 0.35%,0.45% and 0.55% of steel fibre in terms of volume. Compression test and flexural test was implemented which was accordance to the ASTM C-39 and ASTM C-78 respectively. Compression test were tested to cube and flexural test were tested to beam sample.The graphs were used to present the result.Shear strength became increased due to the percentages of the steel fibre.If the percentages of steel fibres were high, the shear strength was also high.The highest value of shear strength, 14.47kN is for 0.55 % which is the highest value of steel fibre reinforcement in this study.With mix of concrete design with percentage of steel fibre reinforcement in term of volume,optimum compressive strength for 7 days of curing at 20.07 N/mm² can be achieved at 0.55% of steel fibre reinforcement.Meanwhile, optimum compressive strength for 28 days of curing at 29.31 N/mm² can be achieved at 0.15% of steel fibre reinforcement. From this study,the usage of steel fiber in concrete will increase the shear strength of the concrete.That’s mean, steel fibre can be use for reduce shear reinforcement in concrete.